2010
DOI: 10.3109/14764172.2010.502460
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser therapy for the treatment of epidermolysis bullosa: A case report

Abstract: Epidermolysis bullosa (EB) is a rare group of diseases characterized by skin fragility. There is no specific treatment, short of protection from trauma, currently available for these patients. Low-level laser therapy (LLLT) was effective as an analgesic and in accelerating cutaneous wound healing after six sessions of therapy in a child with dystrophic EB with cutaneous scarring and blisters on the limbs and trunk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
0
6
0
5
Order By: Relevance
“…In a study by Trelles & Allones, researchers found that the use of LED red light therapy led to significant improvements in patients' wounds, cutting healing time by one-half or one-third when compared to those not treated with LED 8 . Additionally, another study resulted in the conclusion that LLLT was effective in speeding up the healing process of patients' dystrophic epidermolysis bullosa 11 . Lastly, a final study showed some benefit in patients using LLLT to treat unresponsive skin ulcers 12 .…”
Section: Resultsmentioning
confidence: 98%
“…In a study by Trelles & Allones, researchers found that the use of LED red light therapy led to significant improvements in patients' wounds, cutting healing time by one-half or one-third when compared to those not treated with LED 8 . Additionally, another study resulted in the conclusion that LLLT was effective in speeding up the healing process of patients' dystrophic epidermolysis bullosa 11 . Lastly, a final study showed some benefit in patients using LLLT to treat unresponsive skin ulcers 12 .…”
Section: Resultsmentioning
confidence: 98%
“…A FBM tem se mostrado eficiente no tratamento de diversas lesões. Estudos evidenciam resultados importantes no processo da cicatrização de feridas em pacientes diabéticos, queimaduras, epidermólise bolhosa, entre outras (Carvalho et al, 2016;Kazemikazemikoo et al, 2018;Minicucci et al, 2010).…”
Section: Discussionunclassified
“…При поиске в библиографических базах данных найдена одна публикация клинического случая, в которой описано полное заживление язвы (7 см диаметром), существовавшей более 9 мес., у 22-летнего пациента с РДБЭ после двух процедур абляционного фракционного лазерного облучения [64].…”
Section: физиотерапияunclassified